Profesionalisme Oditur Militer Militer Dalam Melakukan Penuntutan - Arief Fahmi Lubis (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2020)
Military justice carried out by the Military Prosecutor is an indirect authority because the delegation of the case is an implementation of the Handover of the Case from Papera, in other words the Military Prosecutor cannot delegate the case or take prosecution action to the competent court without the existence of a Decree from Papera because it is in accordance with Article 123 paragraph (1) letter f of Law Number 31 of 1997, in essence, the authority to hand over cases is the authority of Papera, not the authority of the Military Prosecutor. The aim of this research is to analyze the responsibilities of Military Prosecutors in carrying out prosecutions. Technically, juridically, they are responsible to the TNI Prosecutor General (Orjen TNI), while operationally they are responsible to the Case Submitting Officer (Papera). Qualitative research uses a descriptive approach to collect data systematically, factually, and quickly according to the description at the time of the research. The results of this research show that Military Prosecutors as law enforcers in the field of prosecution in the Military Justice environment have a strategic and decisive role in indicting someone before trial. For this reason, the professionalism of Military Prosecutors is a necessity in carrying out their duties so that prosecutions can be carried out in accordance with applicable regulations and the goal of law enforcement itself can be achieved optimally as expected.